Praktiskā Teoloģija Lu Teoloģijas Fakultātes Studiju Programmās Laikā No 1920. Līdz 1940. Gadam: Practical Theology in the Study Program at the Faculty of Theology in UL 1920-1940. - Geikina, Laima (Cel̜š, 2017)
The article describes the essence of Practical Theology, how it has changed in the course of the previous century, how the Faculty of Theology was established at the University of Latvia at the beginning of the 20th century, and how Practical Theology has integrated in the framework of theological education at the Faculty of Theology. These changes include the redefined role and place of Practical Theology among university study programs. The traditional understanding of Practical Theology requires professional training of pastors according to denominational theological education. The Faculty of Theology was established as a non-denominational institution without a Chair of Practical Theology. When at the beginning of the 20th century the idea to establish a Catholic Faculty emerged the Faculty of Theology started to offer the course of Practical Theology. Liberal policy of the Faculty of Theology was the reason why its relationship with the church remained tense the whole period of time discussed in the article. Nevertheless the Faculty prepared almost 70 % of pastors for the LELC. At the end of the 30s, before the World War II the Faculty of Theology established the Chair of Orthodox Theology.